Aberrant "deep connectivity" in autism: A cortico–subcortical functional connectivity magnetic resonance imaging study. Issue 3 (9th January 2019) - Maximo, Jose O.; Kana, Rajesh K.
Abstract : The number of studies examining functional brain networks in Autism Spectrum Disorder (ASD) has risen over the last decade and has characterized ASD as a disorder of altered brain connectivity. However, these studies have focused largely on cortical structures, and only a few studies have examined cortico–subcortical connectivity in regions like thalamus and basal ganglia in ASD. The goal of this study was to characterize the functional connectivity between cortex and subcortical regions in ASD using the Autism Brain Imaging Data Exchange (ABIDE‐II). Resting‐state functional magnetic resonance imaging data were used from 168 typically developing (TD) and 138 ASD participants across different sites from the ABIDE II dataset. Functional connectivity of basal ganglia and thalamus to unimodal and supramodal networks was examined in this study. Overconnectivity (ASD > TD) was found between unimodal (except for medial visual network) and subcortical regions, and underconnectivity (TD > ASD) was found between supramodal (except for default mode and dorsal attention networks) and subcortical regions; positive correlations between ASD phenotype and unimodal–subcortical connectivity were found and negative ones with supramodal–subcortical connectivity. These findings suggest that brain networks heavily involved in sensory processing had higher connectivity with subcortical regions, whereas those involved in higher‐order thinking showed decreased connectivity in ASD. In addition, brain–behavior correlations indicated a relationship between ASD phenotype and connectivity. Thus, differences in cortico–subcortical connectivity may have a significant impact on basic and higher‐order cognitive processes in ASD. Autism Res 2019, 12: 384–400 © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This study focused on examining the functional connectivity (synchronization of brain activity across regions) of two types of brain networks (unimodal and supramodal) with subcortical areas (thalamus and basal ganglia) in children, adolescents, and adults with autism spectrum disorder (ASD) and how this relates to ASD phenotype. ASD participants showed overconnectivity in unimodal networks and underconnectivity in supramodal networks. These findings provide new insights into cortico–subcortical connections between basic sensory and high‐order cognitive processes.